TANTANGAN DAN PELUANG PROFESI GURU DI ERA GLOBALISASI - Nurul Hasanah; Dhiyaa Aulia Muttaqin, Ikmawati Ikmawati, Zainuddin Untu (CV. ADIBA ASIHA AMIRA, 2025)
This study aims to identify the challenges and opportunities faced by teachers in the era of globalization. Major challenges include integrating technology into teaching, enhancing professional competencies, and adapting to globally influenced curricula that are becoming increasingly complex. Teachers are required not only to educate but also to act as facilitators who guide students in critical thinking, communication, and cultural awareness. This research employs a library research method by analyzing various sources, such as books, journals, and relevant scientific articles. The results indicate that although teachers struggle with adopting technology and implementing digital-based learning, globalization also offers significant opportunities, such as access to global educational resources, the development of innovative teaching methods, and collaboration with educators worldwide. By effectively utilizing technology, teachers can create a more effective, inclusive, and adaptable learning environment. Therefore, improving competencies through training and professional development is crucial in addressing globalization challenges and enhancing the quality of education.